2016
DOI: 10.1117/1.jbo.21.7.075005
|View full text |Cite
|
Sign up to set email alerts
|

Automated cervical precancerous cells screening system based on Fourier transform infrared spectroscopy features

Abstract: Fourier transform infrared (FTIR) spectroscopy technique can detect the abnormality of a cervical cell that occurs before the morphological change could be observed under the light microscope as employed in conventional techniques. This paper presents developed features extraction for an automated screening system for cervical precancerous cell based on the FTIR spectroscopy as a second opinion to pathologists. The automated system generally consists of the developed features extraction and classification stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…By hyperspectral imaging of specific areas of tissue samples, it is possible to achieve a morpho‐chemical correlation between histological and vibrational analysis . The potential offered by FTIR‐HSI to obtain relevant and punctual biomolecular information at molecular level and to detect changes in the biochemical composition and conformation of the most relevant biomolecules on the same sample and at the same time has been already reported in previous studies , investigating prostate , cervix , breast , colon , lung , thyroid and skin tumoral lesions. In some cases, the FTIR‐HSI approach played a key role in detecting early stages of inflammatory and malignant diseases, helping to gain a deeper understanding of the etiologic nature of different pathologies, even before any detectable morphological evidence .…”
Section: Introductionmentioning
confidence: 84%
“…By hyperspectral imaging of specific areas of tissue samples, it is possible to achieve a morpho‐chemical correlation between histological and vibrational analysis . The potential offered by FTIR‐HSI to obtain relevant and punctual biomolecular information at molecular level and to detect changes in the biochemical composition and conformation of the most relevant biomolecules on the same sample and at the same time has been already reported in previous studies , investigating prostate , cervix , breast , colon , lung , thyroid and skin tumoral lesions. In some cases, the FTIR‐HSI approach played a key role in detecting early stages of inflammatory and malignant diseases, helping to gain a deeper understanding of the etiologic nature of different pathologies, even before any detectable morphological evidence .…”
Section: Introductionmentioning
confidence: 84%
“…Three different spectroscopic studies using single cells from LBC samples investigated cervical precancer of low and high grades [64][65][66] . One study highlighted that cytological samples were suitable for analysis of fresh samples or after storage at À25 o C, but not À80 o C [64] .…”
Section: Cervical Cancermentioning
confidence: 99%
“…After comparison of controls with high-grade precancer across all three studies, the sensitivity and specificity were found to be between 86-100% and 90-100% respectively; sensitivity and specificity for detecting low-grade lesions were 94% and 95-98% respectively. The authors proposed an automated screening system for cervical cancer [65] and also highlighted that histological assessment provided higher diagnostic accuracy in comparison to cytological assessment [66] .…”
Section: Cervical Cancermentioning
confidence: 99%
“…Alternatively to the spectral histopathology of tissue sections, spectral cytopathology was carried out for cancer detection in cells exfoliated from oral, nasopharyngeal cavities, the esophagus, the bladder and the cervix [25][26][27]. Such approach does not involve the freeze-drying procedure used for the tissue sections and employs fixatives (typically, solutions of alcohols) with minimal adverse influence [28,29].…”
Section: Introductionmentioning
confidence: 99%